2002
DOI: 10.1039/b2rp90023h
|View full text |Cite
|
Sign up to set email alerts
|

The Learning and Teaching of the Concepts ‘amount of Substance’ and ‘mole’: A Review of the Literature

Abstract: The importance of the concepts of 'amount of substance' and 'mole' is supported by the abundance in the last decade of research papers on the problem of the teaching and learning of these concepts. The present study attempts a review of the relevant bibliography, including recent investigations on both the difficulties of learning these concepts and the didactic alternatives that are provided from different perspectives. The literature reviewed shows that students have great difficulty in handling the above co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 80 publications
1
50
0
9
Order By: Relevance
“…Similar findings emerged in a study of two chemistry teachers in South Africa [72]. In a 2002 review Furió et al concluded that great confusion exists among educators and textbooks about the quantity "amount of substance" and its unit the mole [62]. Moreover students reflect this confusion by seldom using "amount of substance" and frequently conceptualizing and using definitions of the mole as a mass or a number ('Avogadro number').…”
Section: Educational Papers Concerned About the Molementioning
confidence: 63%
See 2 more Smart Citations
“…Similar findings emerged in a study of two chemistry teachers in South Africa [72]. In a 2002 review Furió et al concluded that great confusion exists among educators and textbooks about the quantity "amount of substance" and its unit the mole [62]. Moreover students reflect this confusion by seldom using "amount of substance" and frequently conceptualizing and using definitions of the mole as a mass or a number ('Avogadro number').…”
Section: Educational Papers Concerned About the Molementioning
confidence: 63%
“…Currently, the mole is defined as being that amount of substance which contains as many elementary entities as there are atoms in 0.012 kg of carbon-12 [61]. The number of entities in one mole of substance is related to the Avogadro constant that is in essence a scaling factor between macroscopic and microscopic, particulate quantities [60,62,63].…”
Section: Educational Papers Concerned About the Molementioning
confidence: 99%
See 1 more Smart Citation
“…Pada pokok bahasan stoikiometri, kesalahan konsep yang terjadi meliputi perhitungan perbandingan massa atom dalam molekul [2], penentuan mol suatu senyawa dengan menggunakan koefisien reaksi [3], menentukan reaksi pembatas, dan menghubungkan beberapa konsep dalam penyelesaian soal-soal stoikiometri [4,5] Rendahnya pemahaman mahasiswa terhadap konsep-konsep stoikiometri di atas juga terjadi pada mahasiswa Program Studi Pendidikan Matematika FKIP Universitas Mataram setiap tahun pelajaran, sehingga mempengaruhi prestasi belajar pada mata kuliah kimianya. Data hasil belajar mahasiswa angkatan 2007/2008 untuk pokok bahasan stoikiometri adalah sebesar 50,75% mahasiswa mendapatkan nilai di bawah 65.…”
Section: Cooperative Learning Exchanging Greetings and Questions To Iunclassified
“…(B Hibbert, personal communication). This is not a big improvement since ''Strömdahl et al carried out an interesting study on the concept of mole among educators in 1994 and found that only 11 % identified the mole as the unit of 'amount of substance'' (quoted in [11]). …”
mentioning
confidence: 99%